2022
DOI: 10.1111/are.15844
|View full text |Cite
|
Sign up to set email alerts
|

Dietary selenium requirement of triploid rainbow trout ( Oncorhynchus mykiss ) based on selenium yeast supplementation

Abstract: Selenium(Se) is a biological essential trace element that affects the growth and health of fish. The present study aimed to explore the dietary Se requirement of triploid rainbow trout using Se‐yeast supplement. The levels of Se added to the basal diet were 0(Se0), 0.1(Se0.1), 0.3(Se0.3), 0.5(Se0.5), 1.0(Se1.0), 4.0(Se4.0) and 16.0(Se16.0) mg Se/kg diet respectively. Results showed that the fish fed Se4.0 diet had significantly higher weight gain and lower oxidative stress compared with the fish fed Se16.0 and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 62 publications
1
3
0
Order By: Relevance
“…SEPP, the sole selenoprotein containing multiple selenocysteine residues, predominantly resides in the plasma, where it acts as a transporter of Se to various tissues ( 8 , 49 ). Consistent with previous research in triploid rainbow trout ( 7 ) and Nile tilapia ( 47 ), our study also found higher expression levels of SEPP in fish fed with adequate SePCH, which suggested that dietary SePCH can improve Se transport via SEPP in largemouth bass. SEP15 is localized within the endoplasmic reticulum (ER) lumen, where it can assist in oxidative folding and structural maturation of N-glycosylated proteins for its oxidoreductase activity ( 50 , 51 ).…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…SEPP, the sole selenoprotein containing multiple selenocysteine residues, predominantly resides in the plasma, where it acts as a transporter of Se to various tissues ( 8 , 49 ). Consistent with previous research in triploid rainbow trout ( 7 ) and Nile tilapia ( 47 ), our study also found higher expression levels of SEPP in fish fed with adequate SePCH, which suggested that dietary SePCH can improve Se transport via SEPP in largemouth bass. SEP15 is localized within the endoplasmic reticulum (ER) lumen, where it can assist in oxidative folding and structural maturation of N-glycosylated proteins for its oxidoreductase activity ( 50 , 51 ).…”
Section: Discussionsupporting
confidence: 92%
“…As an essential micronutrient, dietary Se plays crucial roles in promoting growth and maintaining normal physiological functions in different organisms ( 2 , 34 ). Numerous studies have demonstrated that dietary selenium can influence the growth and development of various aquatic and terrestrial animal species, including largemouth bass ( 1 ), European seabass ( Dicentrarchus labrax ) ( 3 ), rainbow trout ( Oncorhynchus mykiss ) ( 7 ), common carp ( Cyprinus carpio ) ( 35 ), grass carp ( Ctenopharyngodon idellus ) ( 36 ) and chicken ( 37 ). In line with these findings, our results also presented that 0.60 and 1.20 g/Kg SePCH (equivalent to 0.84-1.30 mg/kg) notably heightened WG and DGR, highlighting the role of adequate SePCH (0.60 and 1.20 g/Kg) could enhance the growth performance of largemouth bass ( 1 , 3 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations